Development Trends of Islamic Finance Worldwide - Alisher Eshimov (Scientific Trends, 2023)
The Islamic finance industry resiliently grew by 17% in 2021, reaching nearly US$4 trillion in total assets. The growth was evident across sectors including Islamic banking, Sukuk, Islamic funds, and other financial institutions. Notably, Islamic banking, comprising 70% of assets, expanded due to government support, operational efficiency, and strong demand. Net income surged by 290%, while average return on assets also increased. The rise of fully digital Islamic banks globally and responses to the LIBOR transition, such as Malaysia's MYOR-i and Oman's Islamic money market instruments, highlighted industry innovation. Efforts to enhance sustainability, governance, knowledge, and awareness through the Islamic Finance Development Indicator (IFDI) underscore industry progress, positioning Islamic finance for continued growth and innovation.
Keywords: Islamic finance, industry growth, total assets, resilience, sectors, Islamic banking, Sukuk, Islamic funds.